Where Forest Policy and Social Support Collide: Perceptions and Knowledge of Landholders About Forest Management in Central Chile - Zorondo-Rodriguez, F; Abasolo-Farfan, I; Rodriguez-Gomez, G (Springer, 2023)
Public perceptions and knowledge of forestry institutions are key for effective governance. Drawing from research among landholders in Chile through structured questionnaires, we examine the role that knowledge of forest regulations and agencies plays in relation to public perceptions of the forestry agency, and how tenure of forest land affects this association. Multivariate regressions showed a U-shaped relationship between perceptions and knowledge, explained by ownership of forested land. Landholders with more hectares of native forest reported a negative relationship between knowledge and perception, whereas landowners with fewer hectares of native forest reported a positive association. Our results suggest a forest management paradox: forestry institutions are established to sustainably manage and conserve biodiversity, especially for native threatened forests; nonetheless, the perceptions of landholders with greater areas of forest, who should be the targeted partners of these institutions, appear to become more negative as their knowledge of forestry institutions increased. Our results provide key information for adapting forestry institutions to socio-ecological contexts to produce effective outcomes. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2023.